Power of GeoGebra in Igniting the Interest in Learning Quadratic Functions - Pospos, Rhio; Piñero, Brando (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the perceived relationship between students’ interest in learning quadratic functions after utilizing GeoGebra and their perceived usefulness. The study used a quasi-experimental design, specifically the one-group pretest-posttest design using a single-stage cluster sampling technique, to identify Grade 9 students' interest levels before and after using GeoGebra software in the school year 2023- 2024 at Demetrio L. Alviola National (Memorial) High School. It also used the weighted mean, Wilcoxon test, and Spearman rank correlation coefficient to compare pre- and post-evaluation interest in learning quadratic functions. The results showed that GeoGebra effectively increased students’ interest in quadratic functions, igniting a greater passion for the subject matter. Furthermore, using GeoGebra tools increased students' interest in learning, leading to greater confidence, participation, and motivation to understand quadratic functions. This encompassed tasks such as graphing, solving equations, and applying their knowledge to real-world scenarios, representing a significant shift before and after incorporating geometry into the learning process. Certainly, GeoGebra's engaging and vibrant components help students to relax and stay engaged, enhancing the enjoyment and collaboration aspects of education. The findings also showed that students' substantial progress in three areas—understanding concepts, engaging with teachers, and assessment results—is closely associated with their interest in learning more about quadratic functions. Students more enthusiastic about quadratic functions are more likely to comprehend these topics using GeoGebra.